2013
DOI: 10.1038/jcbfm.2013.39
|View full text |Cite
|
Sign up to set email alerts
|

On the Normalization of Cerebral Blood Flow

Abstract: Cerebral blood flow (CBF) is the most common parameter for the quantification of brain's function. Literature data indicate a widespread dispersion of values that might be related to some differences in the measurement conditions that are not properly taken into account in CBF evaluation. Using recent high-resolution imaging of the complete cortical microvasculature of primate brain, we perform extensive numerical evaluation of the cerebral perfusion. We show that blood perfusion associated with intravascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…In order to demonstrate our results we introduced two definitions of voxelwise perfusion, global perfusion P s and local perfusion P v . Local perfusion P v is in line with [ 7 ] where the authors demonstrated a discretization dependent flow without connecting it mathematically to perfusion. Theory and examples in our work show that this definition of perfusion does not comply with the physical understanding of perfusion as a feeding arterial blood flow.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In order to demonstrate our results we introduced two definitions of voxelwise perfusion, global perfusion P s and local perfusion P v . Local perfusion P v is in line with [ 7 ] where the authors demonstrated a discretization dependent flow without connecting it mathematically to perfusion. Theory and examples in our work show that this definition of perfusion does not comply with the physical understanding of perfusion as a feeding arterial blood flow.…”
Section: Discussionsupporting
confidence: 71%
“…It was previously suggested to normalize the flow by surface instead of volume [ 7 ]. Our experiments suggest that a surface normalization is nevertheless discretization dependent, and traditional 1C models are not able to restore this type of perfusion, neither for global, nor for local perfusion (cfr.…”
Section: Discussionmentioning
confidence: 99%
“…34 It is worth noting at this point that the concept of a well-defined absolute blood flow has been questioned as the value of absolute blood flow obtained has been theoretically demonstrated to depend on vascular geometry, measurement procedure, and spatial scale sampled. 35,36 Further research is needed to better understand the implications of these theoretical arguments.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods can be used to measure CBF, such as computed tomography perfusion (CT perfusion), positron emission tomography (PET), and single-photon emission computed tomography; however, CBF measured by different methods normally cannot be compared directly (Kudo et al, 2003; Guibert et al, 2013). In addition to the methods mentioned above, an increasingly popular method to quantify CBF is to use arterial spin labeling (ASL) magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%